True Significance of Mahabharata as a great Epic of India: A Critique - Panda, Narasingha Charan (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 1 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
India is one of the most religiously and ethnically diverse nations in the world, with some of the most deeply religious societies and cultures. Religion plays a central and definitive role in the life of many of its people. Besides, India is the birthplace of Hinduism, Buddhism, Jainism, Sikhism, and other religions. Besides, the Indian literary tradition is the oldest in the world. The earliest works were composed to be sung or recited, and were so transmitted for many generations before being written down. Apart from the Vedas, which are a sacred form of knowledge, there are other works such as the Hindu epics Ramayana and MÁhÁbhÁrata, treatises such as VÁstu ÐÁstra in architecture and town planning, and Artha-ÐÁstra in political science. The most famous works in Sanskrit are the Hindu holy texts like the Vedas, UpaniÒads, and Manusmªti. The MÁhÁbhÁrata is an ancient Indian epic, which is very famous in the world. The Bhagavad GÍtÁ is also a part of this great epic. It is very big in size and covers every subjects of Indian traditions. All the scholars like this epic due to its greatness and different subject matters. However, this paper will deal in brief all about its importance as the scholars speaks and writes since last thousand years.